Understanding Rights Reversion When, Why & How to Regain Copyright and Make Your Book More Available - Schofield, Brianna L. (Authors Alliance, 2015)
Are you an author who would like to increase your book's availability? Have you already entered into a publishing agreement for your book? If you answered yes to both of these questions, then read on! Understanding Rights Reversion addresses the needs of authors who wish to make their works available to a wider audience in ways that may be prohibited by the terms of their existing publishing agreements. For example, this guide will help authors who want to do things like bring their out-of-print books back into print; publish digital versions of their books; make their books openly accessible; publish updated editions of their books; and create new works derived from their books (e.g., translations, audio editions, cinematic adaptions, etc.). Authors who consult this guide will be better informed about strategies for making their books more available.